This Fabulous century, 1870-1900 - Time Life Books (Time-Life Books New York, 1970)
This volume is one of a series that chronicles American culture form 1870 to 1970.
Includes Index and Bibliography
Keywords: Social life and customs -- Pictorial works -- 19th century; History -- 19th century. -- United States